Predictive and proactive fatigue risk management approaches in commercial aviation. (2nd October 2020) - Rangan, Suresh; Riedy, Samantha M.; Bassett, Rob; Klinck, Zachary A.; Hagerty, Patrick; Schek, Ethan; Zhang, Ying; Hursh, Steven R.; Van Dongen, Hans P.A.
ABSTRACT: In commercial aviation, sharing best practices of fatigue risk management (FRM) is important for the industry, its employees, and the community. Chronobiologists and sleep scientists have elucidated the impact of the biological clock and sleep/wake schedules on fatigue and captured their contributions in biomathematical models. The application of these models and other aspects of FRM requires expertise to which not all operators have access. We, therefore, describe some predictive and proactive approaches to FRM, including a collaborative process for evaluating and revising duty schedules to reduce fatigue risk and an innovative wake-up call program to better utilize planned napping opportunities.